2016
DOI: 10.1088/0031-9155/61/21/7688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood activity on dosimetric calculations for radiopharmaceuticals

Abstract: The objective of this work was to investigate the influence of the definition of blood as a distinct source on organ doses, associated with the administration of a novel radiopharmaceutical for positron emission tomography-computed tomography (PET/CT) imaging-(S)-4-(3-F-fluoropropyl)-L-glutamic acid (F-FSPG). Personalised pharmacokinetic models were constructed based on clinical PET/CT images from five healthy volunteers and blood samples from four of them. Following an identifiability analysis of the develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Two sources of uncertainties were investigated: the interindividual variability in the TIACs and the differences among the anatomical models employed for dosimetry. The TIACs were computed based on the individual‐specific pharmacokinetic models in our previous work . The pharmacokinetic models were assumed to be fixed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two sources of uncertainties were investigated: the interindividual variability in the TIACs and the differences among the anatomical models employed for dosimetry. The TIACs were computed based on the individual‐specific pharmacokinetic models in our previous work . The pharmacokinetic models were assumed to be fixed.…”
Section: Discussionmentioning
confidence: 99%
“…The TIACs were computed based on the individual-specific pharmacokinetic models in our previous work. 24 The pharmacokinetic models were assumed to be fixed. Thus, the uncertainties associated with the model structure were neglected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that blood activity has a substantial effect on absorbed doses for highly vascular organs, which are not source regions [40]. As mentioned above, total blood as source region consists of blood vessels and RBVs.…”
Section: Monte Carlo Calculationsmentioning
confidence: 95%